2023
DOI: 10.1038/s41598-023-33288-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning synthesis of cone-beam computed tomography from zero echo time magnetic resonance imaging

Abstract: Cone-beam computed tomography (CBCT) produces high-resolution of hard tissue even in small voxel size, but the process is associated with radiation exposure and poor soft tissue imaging. Thus, we synthesized a CBCT image from the magnetic resonance imaging (MRI), using deep learning and to assess its clinical accuracy. We collected patients who underwent both CBCT and MRI simultaneously in our institution (Seoul). MRI data were registered with CBCT data, and both data were prepared into 512 slices of axial, sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For the 18 original CBCT (oCBCT) and corresponding predicted (or corrected) CBCT (pCBCT) images, the evaluation was conducted using a PACS viewer (Zetta, Tae-young, South Korea) in random order. Two radiologists made an evaluation using a modified version of the clinical CBCT image evaluation chart provided by the Korean Academy of Oral and Maxillofacial Radiology ( Table 2 ) [ 13 ]. The evaluation procedure was conducted individually in blind condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 18 original CBCT (oCBCT) and corresponding predicted (or corrected) CBCT (pCBCT) images, the evaluation was conducted using a PACS viewer (Zetta, Tae-young, South Korea) in random order. Two radiologists made an evaluation using a modified version of the clinical CBCT image evaluation chart provided by the Korean Academy of Oral and Maxillofacial Radiology ( Table 2 ) [ 13 ]. The evaluation procedure was conducted individually in blind condition.…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning (DL) based approaches for CBCT image improvement have recently emerged as a possible viable solution in clinics. While prior studies have demonstrated the possibility of improving CBCT through the use of DL by reducing artifacts and noise and by standardizing pixel intensity [ 6 12 ], DL inference is still limited by obscured anatomic fine details and blurred edges in the image [ 7 , 13 ]. These factors may limit the diagnostic utility of CBCT for intricate features such as the teeth, alveolar bone pattern, sinuses, or the temporomandibular joint (TMJ) complex.…”
Section: Introductionmentioning
confidence: 99%
“…The study’s central tenet is to improve diagnostic accuracy and efficiency by combining High-Resolution Spiral Computed Tomography (HRSCT) [ 16 ] scanning with Deep Learning Techniques (DLT) [ 17 ]. Incorporating the CNN-UNet deep learning method, which has been fine-tuned to perform exceptionally well in catching the finest distinctions inside medical images, is central to this groundbreaking method.…”
Section: Introductionmentioning
confidence: 99%